Genome-Wide Identification and Functional Characterization of the Trans-Isopentenyl Diphosphate Synthases Gene Family in Cinnamomum camphora - Yang, Zerui; Xie, Chunzhu; Zhan, Ting; Li, Linhuan; Liu, Shanshan; Huang, Yuying; An, Wenli; Zheng, Xiasheng; Huang, Song (Frontiers in Plant Science, 2021)
Trans-prenyltransferase (TPTS) genes are known to be important determinants of terpene diversity and the accumulation of terpenoids. The essential oil of the borneol chemotype of Cinnamomum camphora, which is rich in monoterpenes, sesquiterpenes and other aromatic compounds, has a wide range of pharmacological activities and has therefore attracted considerable interest. However, the TPTS gene family in the camphor tree (Cinnamomum camphora [L.] Presl) has not yet been characterized. In this study, we identified 10 TPTS genes in the genome of the C. camphora borneol chemotype, which were unevenly distributed on chromosomes. Synteny analysis revealed that the TPTS gene family in this species likely expanded through segmental duplication events. Furthermore, cis-element analyses demonstrated that C. camphora TPTS (CcTPTS) can respond to multiple abiotic stressors. Finally, functional characterization of eight putative short-chain TPTS proteins revealed that CcTPTS3 and CcTPTS9 exhibit farnesyl diphosphate synthase activity, while CcTPTS1 and CcTPTS2 encode geranylgeranyl diphosphate synthases. Although CcTPTS8 and CcTPTS10 were found to be catalytically inactive alone, they were able to bind to each other to form a heterodimeric, functional geranylgeranyl diphosphate synthase in vitro; this interaction was confirmed using a yeast two-hybrid assay. Furthermore, CcTPTS3, CcTPTS8, CcTPTS9 and CcTPTS10 genes were found to be more active in C. camphora roots compared to stems and leaves, consistent with the expression patterns of most monoterpenoid synthases. Taken together, our results indicate that these synthases are regulated by one heterodimeric geranylgeranyl diphosphate synthase and two farnesyl diphosphate synthases in the camphor tree. These novel results provide a foundation for further exploration of the role of the TPTS gene family in camphor trees, and provides a potential mechanism by which the production of camphor tree essential oil could be increased for pharmacological purposes through metabolic engineering.